Quicksand : a novel - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2008)
Forensic sculptor Eve Duncan is still obsessed with finding her daughter, Bonnie. No stranger to looking for clues where there seem to be none, Eve enlists the unique skills of the mysterious Dr. Megan Blair to help bring Bonnie's elusive killer to justice. The tension and danger escalates as Eve and Joe Quinn go on a hunt that can either bring them the revenge and closure that Eve has long sought or the destruction of everything she holds dear.